Synthesis of Pentasaccharide Repeating Unit Corresponding to the Cell Wall O-Polysaccharide of Salmonella enterica O55 Strain Containing a Rare Sugar 3-Acetamido-3-deoxy-d-fucose - Gucchait, Arin; Kundu, Monalisa; Misra, Anup Kumar (Synthesis, 2021)
A pentasaccharide repeating unit corresponding to the cell wall O-antigen of Salmonella enterica O55 containing a rare sugar, 3-acetamido-3-deoxy-d-fucose has been synthesized as its p-methoxyphenyl glycoside using a sequential stereoselective glycosylation strategy. A suitably functionalized 3-azido-3-deoxy-d-fucose thioglycoside derivative was prepared in very good yield and used in the stereoselective glycosylation reaction. Functionalized monosaccharide intermediates were prepared judiciously and stereoselectively assembled to get the desired pentasaccharide derivative in excellent yield.
Keywords: pentasaccharide; glycosylation; 3-acetamido-3-deoxy-d-fucose; Salmonella enterica; stereoselective